Prix de Lausanne, 2001 A report - Wade, Kathryn (Dance Books Ltd., Alton,Hampshire (UK), 2001)
PALABRAS CLAVE: international competition dancers, Prix de Lausanne, 2001, John Neumeier, Jaime Garcia Castilla.